Evaluation of Sun- and Daylight Availability in Early Stages of Design Development - A Method Based on Correlations of Interior and Exterior Metrics - Jacobsson, Emma; Eriksson, Fredrik (My University, 2017)
is of great importance to evaluate a building development in early stages of design, in order to fulfil current building regulations on energy performance and comfort. There are several simulation methods, which are meant to focus on early design analyses, though results are often only possible to achieve in later stages of design, due to the limitations of input data. Simulations with regard to solar heat gains and daylight calculations are incorporated into the design later on, leading to design issues which could be impossible to solve. The purpose of this Master’s thesis is therefore to develop a methodology that with simple 3D models and input data can provide reliable indications of a building’s performance with regard to sun- and daylight availability, in the earlier stages of design. Additionally, the energy performance of a design is assessed through the mean value of the thermal transmittance. By implementing this type of simulation tool in the design process of city planning, it would be easier to set the prerequisites for an urban area, based on the conditions on site. This would lead to issues being revealed and solved directly. Setting reasonable visions for new building developments, which are possible to achieve, would lead to a more sustainable densification. The choice of simulation methodology is based on an extensive literature review of the workflow of existing calculation software. Choosing the most important performance metrics, which also are possible to simulate in early evaluations of building development, led to the choice of simulation structure. An additional investigation of a correlation between the Daylight Factor and an exterior metric enabled the evaluation of daylight availability in early design stages. The developed simulation methodology has been verified through two representative case studies, though it needs further validation in order to establish the correctness of the methodology compared to a detailed calculation. However, it provides indications that could be useful for evaluating building development and the chances for it to facilitate the design process are considered to be promising.
Keywords: Materialvetenskap; Byggnadsteknik; Materials Science; Building engineering